THE CONCEPT «WORD AND SPEECH» IN RUSSIAN AND UZBEK PROVERBS: A COMPARATIVE LINGUOCULTURAL ANALYSIS - Davlatmuratov Siroj Ravshanbekovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The article presents a comparative linguocultural analysis of the concept «Word and Speech» as represented in the paremiological fund of the Russian and Uzbek languages. A corpus of 140 paremiological units (70 Russian and 70 Uzbek) was selected by continuous sampling from authoritative lexicographic sources. The study identifies both universal and ethnoculturally specific features of the verbalization of this concept. In the Uzbek linguistic picture of the world, the concept of word (so’z) is primarily associated with social responsibility, communal honour, and the sacred power of speech as a binding pledge. In Russian paremiology, the concept of speech is realized through pragmatic irony, the contrast between silence and verbosity, and the idea of the irreversibility of the spoken word. The results contribute to a deeper understanding of the axiological foundations of speech behaviour in both linguocultures.